Research to Discover What Factors Influence the Regular Newspaper Reading Habits of the Public Servants Serving in the Metro Jaffna Region - Umashankar, L. (University Librarians' Association of Sri Lanka, 2016)
Endeavour to promote and popularize the newspaper reading habit, among public servants, by researching talents, individually and collectively. Reading is a basic human skill involving the reader's eyes, his mind and the matter being read. General reading gives an individual, wide perspective of the world and its peoples. One of the major goals of the research is to inspire a knack for reading and to promote a reading culture among its users. The present study aims to investigate the reading habits of the public servants and their gender variability. To this end, 320 public servants were randomly interviewed, who are serving in the Jaffna Metro region to assess their reading habit and to size up how exactly this particular exercise can be honed and improved. Out of the 320 interviewed a 150werefemales and the balance 170 were males. A structured questionnaire had three features. One being open ended; the second was open ended with prequalifying statements and the third Dichotomous choice. The data was analyzed under the Probit model. The model was statistically significant at 1% a level (LR Chi sqr 5.52, Prob> Chi sqr 0.0009, Log likelihood-82.4357 & Pseudo Rsqr 0.088). The model revealed the following factors such as age of the respondent, education, household size, parental educational level, being accessible to social media network and attitude towards knowledge gathering significant for Newspaper reading at 5% a level. It was also found that being a member of a social media network and having large family size affect the Newspaper reading habit negatively. Meanwhile the socio economic factors of the family such as age, parental education, income level and educational level of respondents have great positively significant impact on Newspaper reading habit of public servants. Gender was treated as a dummy variable in the model, but was not found to be significantly influencing the paper reading habit. Besides, the general statistics revealed that among the samples examined about 60% read papers regularly and 90% of these prefer reading in the early mornings. Further the majority prefer Newspaper reading at home as the first option and as the second they prefer to read at the offices. About 78% of the total numbers of officers have access to social media network. About 56% of these are regular readers of the dailies. The remaining 44% believe that regular Newspaper reading is not essential as they have access to social media network. The main conclusion drawn is that, electronic media networking are spellbinding public officers slowly and sooner or later the Newspaper reading habit may become obsolete.
Keywords: Jaffna; Newspaper reading habit; Public servants; Probit model; Social Media Network